Pulmonary artery and right ventricle function in patients with bicuspid aortic valve - Geçmen, Çetin; Güler, Gamze Babür; Hatipoğlu, Suzan; Kahyaoğlu, Muzaffer; Çap, Murat; İzci, Servet; Önal, Çağatay; Erdoğan, Emrah; Hakgör, Aykun; Candan, Özkan; Kalaycı, Arzu; Unkun, Tuba; et al. (My University, 2017)
Objective: Bicuspid aortic valve (BAV) is a complex developmental anomaly caused by abnormal aortic leaflet formation during valvulogenesis. The present study is an assessment of the effects of BAV disease on the ascending aorta and pulmonary artery (PA), and an evaluation of the consequences for systolic and diastolic functioning of the left and right ventricles.?Methods: Total of 66 patients were eligible for inclusion. Pulmonary artery maximum diameter (PAD) was obtained 1 cm distal to the pulmonary annulus. Using pulsed-wave tissue Doppler imaging, left ventricular (LV) early diastolic velocity (E?) measurement was obtained at the annulus with placement of sample volume. Right ventricle (RV) peak global strain rate during systole (RV-SRS), early diastole (RV-SRE), and late diastole (RV-SRA) were calculated.?Results: In this study, 40.9% (n=27) of patients were female and average age was 35±11years. RV-SRS values (?=-.781, t=-2.723; p=0.010) and log-LV tissue Doppler imaging E’ (?=2.996, t=-5.405; p=<0.001) were negatively correlated, and log-PAD (?=4.861, t=3.052; p=0.005) was positively and independently correlated with ascending aortic diameter.?Conclusion: Ascending aorta diameter is positively correlated with PA diameter in BAV patients, and RV strain rate and LV diastolic parameters are affected before development of the valve disease.

Amaç: Biküspit aort kapağı, valvulogenez sırasında anormal aorti kapakçık oluşumu sonucunda ortaya çıkan gelişimsel bir anomalidir. Bu çalışmada, biküspit aort kapak hastalığının pulmoner arter ve çıkan aortaya etkileri, bu durumun sağ ve sol ventrikül sistolik ve diyastolik fonksiyonları üzerine etkisi değerlendirildi.Yöntemler: Çalışmaya 66 hasta dahil edildi. Pulmoner arter en yüksek çapı (PAD), pulmoner anulusun 1 cm distalinden ölçüldü. Sol ventrikül (LV) erken diyastolik hızı, örnek hacim anulusa yerleştirilerek elde edildi. Sol ventrikül (LV) erken diyastolik hız (E'), doku Doppler görüntüleme tekniği kullanılarak ve örnek hacim anulusa yerleştirilerek elde edildi. Sağ ventrikül (RV) pik global strain hızı sistol (RV-SRS), erken diyastol (RV-SRE) ve geç diyastolde (RV-SRA) ölçüldü.Bulgular: Hastaların %40.9'u (n=27) kadın ve ortalama yaşları 35±11'di. Sağ ventrikül sistolik pik global strain hızı (?=0.781, t=-2.723; p=0.010) ve log-LV E' (?=-2.996, t=-5.405; p=<0.001) değerlerinin çıkan aorta çapı ile negatif, log-PAD (?=4.861, t=3.052; p=0.005) değerlerinin ise pozitif ve bağımsız ilişkili olduğu saptandı. Sonuç: Biküspit aort kapaklı hastalarda çıkan aort çapı ile pulmoner arter çapı arasında pozirtif bir korelason olduğunu ve RV strain hızı ve LV diyastolik parametrelerinin kapak hastalığı gelişmeden önce etkilendiğini saptadık.
Biküspit aort kapaklı hastalarda pulmoner arter ve sağ ventrikül fonksiyonları
Keywords: Aortic Valve; Bicuspid; Strain Rate; Aort Kapak; Biküspit; Strain Hızı